Iron and Ferritin Levels in Saliva of Patients with Thalassemia and Iron Deficiency Anemia - Canatan, Duran (Università Cattolica del Sacro Cuore, 2012)
Most of the techniques for measuring iron stores such as serum iron concentration, iron binding capacity, serum ferritin level, liver biopsy can be troublesome or invasive for patients with thalassemia. The salivary iron measurement could be of potential advantage being an easy and non invasive approach for diagnosis of iron deficiency and iron overload . The aim of this study was to compare the levels of iron and ferritin in saliva and serum of patients affected by thalassemia or iron deficiency anemia. For this purpose, 96 patients with iron overload (71 with thalassemia major, 10 with thalassemia intermedia and 15 with thalassemia trait), 30 patients with iron deficiency anemia, and 35 healthy children as control group were involved in this study. Their saliva and serum iron and ferritin levels were measured. Iron and ferritin levels were higher in iron overload groups than in control group and lower in iron deficiency group (p<0.05). Furthermore serum and saliva iron and ferritin levels paralleled in all groups. In conclusion, iron and ferritin saliva can be routinely used for diagnosis of both iron overload and deficiency; furthermore this procedure may be an important advantage for blood donors being easily available and not invasive.